Are new antiretroviral treatments increasing the risks of clinical obesity? - Andrew Hill; Laura Waters; Anton Pozniak (Elsevier, 2019)
There is growing evidence that the use of integrase inhibitors could lead to statistically significant increases in body weight and even clinical obesity, although it is unclear whether these changes are clinically significant. The effects of integrase inhibitors on body weight need to be analysed for women and by race, because current evidence suggests different effects. Potential additional effects of NRTIs on body weight need to be evaluated. Combined, standardised analyses of Phase 3 and independent clinical trials, with endpoints following the US Food and Drug Administration (FDA) guidelines where feasible, should be conducted to answer this question definitively. Analyses should also include a range of laboratory markers of cardiovascular risk, as proposed by the FDA.